The Diversity of Serum Anti-DSG3 IgG Subclasses Has a Major Impact on Pemphigus Activity and Is Predictive of Relapses After Treatment With Rituximab - Golinski, Marie-Laure; Lemieux, Alexandre; Maho-Vaillant, Maud; Barray, Marion; Drouot, Laurent; Schapman, Damien; Petit, Marie; Hertl, Michael; Boyer, Olivier; Calbo, Sébastien; Joly, Pascal; Hébert, Vivien (Frontiers in Immunology, 2022)
Introduction: We studied the distribution and in vitro pathogenicity of anti-DSG3 IgG subclasses during the course of pemphigus vulgaris (PV). Methods: We longitudinally studied the distribution of anti-DSG3 IgG subclasses (before versus after treatment) in sera from PV patients, using an Addressable-Laser-Bead-ImmunoAssay (ALBIA). The in vitro pathogenicity of corresponding sera was tested using keratinocyte dissociation and immunofluorescence assays. Results: Sixty-five sera were assessed at baseline (33 from patients treated with rituximab (RTX) and 32 with corticosteroids (CS)). Sixty-three percent of these baseline sera contained 2 or more anti-DSG3 IgG subclasses versus 35.7% of sera from patients in CR and 75.0% of sera from patients with persistent disease activity after treatment. IgG4 was the most frequently detected anti-DSG3 IgG subclass, both in patients with disease activity and in those in CR. The presence of three or more anti-DSG3 IgG subclasses was predictive of relapse, in particular when it included IgG3, with a positive-predictive-value of 62.5% and a negative-predictive-value of 92%. While anti-DSG3 IgG4 Abs from sera collected before treatment were most often pathogenic, anti-DSG3 IgG4 from sera collected after treatment were pathogenic only after adjusting their titre to the one measured before treatment. Anti-DSG3 IgG3 Abs also had an in vitro pathogenic effect. The disappearance of the pathogenic effect of some sera after removal of anti-DSG3 IgG3 suggested an additional effect of this IgG subclass. Conclusion: The serum levels and number of anti-DSG3 IgG subclasses drive the pathogenic effect of pemphigus sera, and may predict the occurrence of relapses.